Implementasi Manajemen Pendidikan Karakter Dalam Perspektif Pendidikan Islam Di SMP PGRI 1 Kediri - Moh Hasan Firghol (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Recently, the term character education has emerged. Character education has received a lot of attention from Indonesian society. This is because people feel social inequality in educational outcomes. This inequality can be seen from the behavior of current formal education graduates, for example corruption, free sex, drugs and brawls between students. One of the current problems is the low quality of education. This influences student development. This phenomenon is caused by a lack of instilling strong character education management in students. Therefore, character education is needed from the start, namely from childhood. The aim of this research is to describe the implementation of character education management from an Islamic perspective, and to determine the efforts made in implementing character education management from an Islamic perspective. This research is qualitative research, the method used by researchers to obtain data is by 1). Observation. 2). Interview. 3). And documentation. The results of the research show that in Character Education Suhari Ningsih, she always reflects on how to behave well and politely to students and teaches them to speak well.